Receptor Mincle promotes skin allergies and is capable of recognizing cholesterol sulfate - Kostarnoy, Alexey V. (Proc Natl Acad Sci U S A, 2017)
Sterile (noninfected) inflammation underlies the pathogenesis of many widespread diseases, such as allergies and autoimmune diseases. The evolutionarily conserved innate immune system is considered to play a key role in tissue injury recognition and the subsequent development of sterile inflammation; however, the underlying molecular mechanisms are not yet completely understood. Here, we show that cholesterol sulfate, a molecule present in relatively high concentrations in the epithelial layer of barrier tissues, is selectively recognized by Mincle (Clec4e), a C-type lectin receptor of the innate immune system that is strongly up-regulated in response to skin damage. Mincle activation by cholesterol sulfate causes the secretion of a range of proinflammatory mediators, and s.c. injection of cholesterol sulfate results in a Mincle-mediated induction of a severe local inflammatory response. In addition, our study reveals a role of Mincle as a driving component in the pathogenesis of allergic skin inflammation. In a well-established model of allergic contact dermatitis, the absence of Mincle leads to a significant suppression of the magnitude of the skin inflammatory response as assessed by changes in ear thickness, myeloid cell infiltration, and cytokine and chemokine secretion. Taken together, our results provide a deeper understanding of the fundamental mechanisms underlying sterile inflammation.